Acute Panmyelosis with Myelofibrosis - A Rare Subtype of Acute Myeloid Leukemia - Tathagata Chatterjee; Srishti Gupta; Ajay Sharma; Sanjeevan Sharma; Devika Gupta (Mediterranean Journal of Hematology and Infectious Diseases, 2013)
One case of acute panmyelosis with myelofibrosis (APMF) is being reported. A 45 year old male presented with abrupt onset of rapidly progressing low backache, weakness and pancytopenia. On examination there was no organomegaly. Peripheral blood examination revealed normocytic normochromic red blood cells with 10% circulating blasts. Flowcytometric examination of peripheral blood revealed blasts which were positive for CD 34 ,HLA- DR and myeloid associated antigens (i.e. CD13 and CD33).Blasts were negative for anti MPO. Bone marrow aspirate resulted in a dry tap. Bone marrow biopsy revealed panmyeloid proliferation with scattered blasts which were CD 34 positive on imunohistochemistry and negative for anti MPO. Reticulin stain showed grade III myelofibrosis (WHO). Differential diagnosis considered included AML-M7, MDS-RAEB II and AML with myelodysplasia . He was started on chemotherapy [idarubicin and cytarabine; 3+7 induction regimen followed by three cycles of HIDAC (High dose cytosine arabinoside)] after which patient was in complete morphological remission with markedly reduced bone marrow fibrosis. He is now being worked up for allogeneic stem cell transplantation. Patient is asymptomatic at eight months of diagnosis. In conclusion these patients should be managed aggressively with AML therapy and this case report reaffirms the fact that APMF is subtype of AML.